Kemoterapötiklerin erkek üreme sistemi üzerindeki yan etkileri ve koruyucu stratejiler (Adverse effects of chemotherapeutics on male reproductive system, and protective strategies) - Türk, G (My University, 2013)
Although cytotoxic chemotherapy is an effective method for the treatment of many cancer types, it causes numerous adverse effects on the body. Infertility is also one of the most prominent side effects of chemotherapeutic drugs on both females and males. Impotence, oligo-, azoo-, asthenozoo- and teratozoo-spermia, disturbances in testicular structure, spermatogenesis and steroidogenesis, the changes in gonadotrophin levels, damages in sperm DNA and chromosomes, and even exact sterility are the reported side effects induced by chemotherapy in both males with cancer and healthy experimental animals. To prevent the gonadotoxic effects of chemotherapeutics in males, several modalities such as hormone and antioxidant administrations, sperm and germ cell cryopreservation are used. In this review, the data about the adverse effects induced by chemotherapeutics, which are commonly used in cancer treatment, in reproductive organ, tissue and cells in both males with cancer and healthy experimental animals and, also knowledge related to the preventive or protective strategies against these side effects are presented.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Antioxidant chemotherapeutics cryopreservation oxidative stress sperm testis